Determinantes Sociales de la Salud: postura oficial y perspectivas críticas (2013)
ABSTRACT: The relationship between socioeconomic inequalities and the health-disease process has long been demonstrated. Its study and possibilities for intervention have been submitted to analysis by academic and institutional actors which take more or less critical stances depending on their paradigms. In order to analyze the causes of health inequities and provide some recommendations, the World Health Organization established the Commission on Social Determinants of Health in 2005. Latin American El análisis de la salud desde la perspectiva de los determinantes-determinación social de la salud approaches such as Social Medicine and Collective Health recognize the concern of the World Health Organization, yet they strongly criticize the position taken by the Commission, and organize the discussion around the conceptual, ethical and political action axes; in addition, and unlike the Commission, they propose to search for the causes of inequity and its solution in the meaning of social determination. Likewise, authors such as Vicente Navarro also questioned the Commission’s approach to social determinants. For Navarro, it is not inequalities that kill people, but the actors responsible for those inequalities. He also draws the attention towards the hidden power relationships and the entities responsible for inequity and those benefitting from it. Finally, in order to analyze the social determination and the hierarchical location of the social determinants of a particular problem, the issue of hunger is presented as embedded in a reproduction-determination cycle that makes it possible to locate the specificity and generality that are in constant interplay.